THE ROLE OF ACCOUNTING POLICY IN ENSURING THE RELIABILITY OF FINANCIAL STATEMENTS - Muhammadi Israpilovich Khaitboev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Accounting policies play a critical role in determining the quality and reliability of financial statements. This paper explores how well-defined and consistently applied accounting policies contribute to transparent and accurate financial reporting. The study draws on international accounting standards, particularly IFRS, and national regulatory frameworks to examine the influence of accounting policies on stakeholders’ confidence. Methodologically, this research involves qualitative analysis of selected financial statements and policy documents from various organizations. The results highlight that clear and stable accounting policies significantly reduce reporting ambiguity and enhance decision-making by investors and regulators.